Nodular scabies. - Echeverría-García, B.; Tardío, J.C.; Freites, A.; Puente, N.; Borbujo, J. (European Journal of Pediatric Dermatology, 2016)
Nodular lesions mimicking cutaneous mastocytosis can appear as the only manifestation of scabies or as reactive lesions after complete scabies´ treatment. It is important to recognize both situations for making a correct diagnosis and treatment. A case of a 13-month-old boy with brownish nodules 3 months after a familial episode of scabies treated with permethrin was reported. Due to diagnosis doubts a skin biopsy was carried out; the latter ruled out the diagnosis of mastocytosis leading to the final diagnosis of scabies.